Design of a didactic situation – mathematical experiments in linear algebra - Pedersen, Thomas Vils (NOMAD Nordic Studies in Mathematics Education, 2007)
We describe how we used Brousseau’s theories of didactic 1 situations and didactic engineering as a framework for the development of an exam project in a first year mathematics course at a life science university. The main learning goals of the project were to (re)discover eigenvalues and eigenvectors partly by studying the asymptotic behaviour of matrix models for population growth and to understand the role eigenvalues play in such models. Moreover, the students would gain experience with mathematical experiments with the use of computers and with drawing conclusions from such experiments.